Eton college. Szkic do portretu brytyjskiej elitarnej edukacji - Gromkowska-Melosik, Agnieszka (Wydawnictwo Naukowe UAM, 2014)
The article is devoted to the analysis of the social functions of the British public school Eton College, one of the most widely recognized elite schools in the world. Knowing the history of this school is necessary to understand not only the modern educational system of Great Britain, but also a number of social, economic, political, and cultural contexts of the country's development. Eton College is closely associated with the emergence of British civilization and British national identity, especially because boarding public schools such as Eton College not only play the educational role, but also create culture. According to many scholars of education, this college serves the upper class and the aristocracy, providing its graduates privileged access to university at a higher level (elite universities). Nowadays Eton College is still perceived as a bastion of reproduction of male elites.
Eton college. Sketch for a portrait of the British Elite Education
Keywords: elite education; Eton College; public British schools; masculinity